Comment on: Match analysis of U9 and U10 English Premier League academy soccer players using a global positioning system: Relevance for talent identification and development - Carling, C.; Collins, D. (The Journal of Strength and Conditioning Research, 2017)
We read with interest the recent article written by Goto et al. (8): "Match Analysis of U9 and U10 English Premier League Academy Soccer Players using a Global Positioning System: Relevance for Talent Identification and Development." We welcome the idea underpinning this study as a limitation of research in the area of talent identification and development processes is the absence of performance assessments from within the "open" competitive environment (9,10). In summary, the authors reported time-motion analysis data from match play showing that players who were eventually retained by their Academy over the following 2 seasons covered a significantly greater distance overall and in low-speed running in comparison to peers who were released. Consequently, the authors discussed their results in the context of talent identification and development processes. In light of their findings and discussion, however, and a number of flaws apparent therein, it is of our opinion that further debate in the context of the current body of literature is necessary.